Preferential flow in the understory soil of Hippophae rhamnoides at different stump heights - Liu, Lu; Liu, Xiaoyu; Yao, Yunfeng; Qi, Wei; Guo, Yuefeng (Frontiers in Environmental Science, 2023)
This study was aimed to clarify the effects of stumping on the preferential flow of understory soils in Hippophae rhamnoides and to assess what stump heights are appropriate to optimize the preferential flows. Root properties, soil properties and preferential flow of H. rhamnoides at different stump heights (0, 10, 15, 20 cm, and no-stumping, marked as S1, S2, S3, S4, CK respectively) were studied by using in-situ dye tracing and laboratory analysis. Results showed that the stumping significantly increased the preferential flow development. The increasing effect was maximized in S3, as the dye-tracing coverage (DC), maximum dye depth (MaxD), uniform infiltration depth (Unifr), preferential flow ratio (PFfr) and length index (LI) were 36.77%, 40.02 cm, 14.28 cm, 23.85% and 96.72% respectively. The root length density (RLD), root mass density (RMD), root surface area density (RASD), soil water content (SWC), soil total porosity (TP), mean weight diameter (MWD), and soil organic matter (SOM) all ranked as S3>S2>S1>S3>CK, but root average diameter (RAD) changed as S3